2012
DOI: 10.1136/heartjnl-2012-302419
|View full text |Cite
|
Sign up to set email alerts
|

No relation between coronary artery disease or electrocardiographic markers of disease in middle age and prenatal exposure to the Dutch famine of 1944–5

Abstract: We see no relation between prenatal famine and adult CAD, Framingham risk, or any ECG predictors of increased cardiac disease risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 45 publications
(39 reference statements)
1
30
1
Order By: Relevance
“…C. Ravelli et al, 1998; Ravelli, van der Meulen, Osmond, Barker, & Bleker, 1999; Stein et al, 2007) Taken together, clinic-based studies on cardiovascular risk do not show a relation with famine. (Lumey, Martini, Myerson, Stein, & Prineas, 2012; Roseboom et al, 2000) Survival data from one clinic population was recently become published (Van Abeelen et al, 2012) but those results are hard to interpret because of limited sample size. Increases in weight and diabetes prevalence have been confirmed in a comprehensive review of morbidity outcomes from prenatal famine studies world-wide as discussed elsewhere.…”
Section: Introductionmentioning
confidence: 99%
“…C. Ravelli et al, 1998; Ravelli, van der Meulen, Osmond, Barker, & Bleker, 1999; Stein et al, 2007) Taken together, clinic-based studies on cardiovascular risk do not show a relation with famine. (Lumey, Martini, Myerson, Stein, & Prineas, 2012; Roseboom et al, 2000) Survival data from one clinic population was recently become published (Van Abeelen et al, 2012) but those results are hard to interpret because of limited sample size. Increases in weight and diabetes prevalence have been confirmed in a comprehensive review of morbidity outcomes from prenatal famine studies world-wide as discussed elsewhere.…”
Section: Introductionmentioning
confidence: 99%
“…Schreier et al found a protective effect from exposure to war and coronary heart disease: exposed women between 63 and 80 years and men between 50 and 54 years of age had higher survival rates than the unexposed (Schreier et al 2011). Other studies of famine found no increase in coronary artery disease (Lumey et al 2012), no effect on blood pressure (Roseboom et al 1999), no increased cardiovascular mortality (Ekamper et al 2015), and a weak but significant increase in hypertension prevalence among the exposed (OR 1.44, 95 % CI 1.04, 2.0) (Stein et al 2006).…”
Section: Resultsmentioning
confidence: 91%
“…This suggests that the protective effect of caloric restriction in adulthood and animals on atherosclerosis and metabolic syndromes44 45 may not be readily translated to undernutrition in early life. Caloric restriction in different periods of life probably has different effects on atherosclerosis development, as suggested by findings from two studies on the Dutch famine which showed that famine exposure during adolescence increased the risk for cardiovascular events,14 whereas prenatal famine exposure did not 46…”
Section: Discussionmentioning
confidence: 99%